Living Qur’an dan Hadis dalam Menangkal Radikalisme Agama di Sekolah (Studi Kasus Pendidikan Agama Islam di SMA 1 Pleret) - Suismanto (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2018)
Radicalism has caused damage, resulting in many casualties. Efforts to prevent radicalism are the right choice compared to taking action. Counteracting radicalism through living Qur'an Hadith in schools is one of the prevention efforts. Islamic high school education has become the spearhead of efforts to counteract religious radicalism in the youth segment. Through the Living Qur'an and hadith, it is able to increase Muslim awareness of their religious teachings. Prevention of radicalism in schools is an urgent opportunity to do. This research is a qualitative research which describes the implementation of Living Qu'ran and Hadith in schools. Covers policies, teachers, students and practical field experience students. Vision and mission of schools in schools in warding off radicalism. Data collection techniques using observation, documentation and interviews. Researchers used triangulation as a technique to check the validity of the data. The results showed that the prevention of radicalism was carried out systemically. The involvement of all system components in schools starts from establishing the vision and mission of the school. The school has a vision that is in line with the application of the living Qur'an and Hadith. There is involvement of teachers, students practicing field experiences and the students themselves. Existing activities are morning tadarus, dhuha prayer, dhuhur cult, the installation of al-Qur'an verses and Hadith in the school environment, and social service.